20 anniversary of IweTel mailing list - Baiget, Tomí s (Anuario ThinkEPI, 2014)
The article analyses the IweTel mailing list about Library and Information Science in its 20 anniversary. With so many social networks, communication platforms and collaborative work methods, the merits of e-mail distribution lists, whether monodirectional newsletters or discussion forums, are questioned in the 2.0 world. Do they still make sense or are they obsolete? Given the large number of mailing lists that are working effectively, and seeing their evolution over the recent years, the author concludes that mailing lists will survive for many more years.
Keywords: Mailing lists; Discussion forums; Web 2.0 environment; Trends; Library and information science; Information professionals; Iwetel.